E-MAGAZINE TENTANG KULINER LEGENDARIS DI SURABAYA - Pharamaraditya, Ghifarry Rachmadhan; Nisa, Diana Aqidatun; Romadhona, Mahimma (Universitas Negeri Makassar, 2024)
The issue of post-colonial food, like the basic national attributes mentioned at the beginning of this article, is not just a basic need for society. However, food also experienced a process of nationalization. Culinary which is the highlight in this article, is etymologically a translation of the English word 'culinary'. This word comes from the Latin 'culinarius' which is derived from the word 'culina' which means kitchen, a place to cook food. Cooking has a universal meaning, namely the transformation from nature to culture. Food can be said to be the bond that separates one community from another. When away from home, food can convey a sense of belonging in an unfamiliar world. Food can serve as a key to bond. Culinary is a concept about food, thus culinary is an element of culture, which is related to historical roots, colonialism, myths, religion and some values in a society. Culinary there is evidence of a process of cross-cultural communication, in accordance with the influence of globalization. This culinary tour is one of the main destinations for tourists within the city and tourists outside the city because Surabaya City is a transit city. Besides that, Culinary tourism in Surabaya has several cultures, some from Legendary, Chinese, western, etc. For legendary culinary tourism, especially in Surabaya, there are several examples, namely Lontong Balap Pak Fat, Lontong Balap Rajawali, Pak Jayen's Egg Tofu, Mixed Tofu, and many more. In conducting research on this design using qualitative methods. The method used uses two approaches, namely interviews and observation. After determining the method to be used in this design, the method produces a design concept with the keyword